Sclerosing epithelioid fibrosarcoma of the foot: A case report. Issue 4 (21st April 2023) - Mremi, Alex; Sadiq, Adnan; Goodluck, Gregory; Lodhia, Jay
Abstract: Sclerosing epithelioid fibrosarcoma (SEF) is a rare and distinctive variant of fibrosarcoma. To date, about 100 cases only have been documented. Histopathologically, it resembles a variety of benign, pseudosarcomatous and other malignancies. Early diagnosis and treatment are vital for improving the treatment outcomes. Abstract :